The Role of Creative Social Energy in Strengthening Ecological Adaptation Capacity Through Community Empowerment - Sumardjo Sumardjo; Adi Firmansyah; Leonard Dharmawan (Jurnal Penyuluhan, 2020)
Investments in large companies engaged in natural resource management have the potential to cause conflict, which requires an alternative model of conflict potential management. This study aims to analyze the development of creative social energy as an alternative to managing potential conflicts through empowering community food security. This study uses a participatory action study method for community empowerment and cybernetic triangulation methods in extracting data. Communities in the company's operational Ring1 area carried out community empowerment efforts by placing extension workers as community assistants. The results of the study show that community empowerment through a participatory extension approach is effective in supporting the realization of community welfare through increased income. Participatory community empowerment is effective in developing creative social energy. There is a close relationship between community empowerment and strengthening creative social energy and increasing the ecological adaptation capacity of society to the dynamics of environmental change. The ecological adaptation capacity of the community develops in line with the level of community empowerment. Community empowerment through effective participatory counseling is a model for managing potential conflicts in CSR programs. Extension workers with participatory community empowerment competencies are a key factor in the success of community empowerment.